Age- and Tissue-Specific Expression of Senescence Biomarkers in Mice - Hudgins, Adam D.; Tazearslan, Cagdas; Tare, Archana; Zhu, Yizhou; Huffman, Derek; Suh, Yousin (Frontiers in Genetics, 2018)
Cellular senescence is a state of irreversible cellular growth arrest accompanied by distinct changes in gene expression and the acquisition of a complex proinflammatory secretory profile termed the senescence-associated secretory phenotype (SASP). Senescent cells accumulate in aged tissues and contribute to age-related disease in mice. Increasing evidence that selective removal of senescent cells can ameliorate diseases of late life and extend lifespan in mice has given rise to the development of senolytics that target senescent cells as anti-aging therapeutics. To realize the full potential of senolytic medicine, robust biomarkers of senescence must be in place to monitor the in vivo appearance of senescent cells with age, as well as their removal by senolytic treatments. Here we investigate the dynamic changes in expression of the molecular hallmarks of senescence, including p16Ink4a, p21Cip1, and SASP factors in multiple tissues in mice during aging. We show that expression of these markers is highly variable in age- and tissue-specific manners. Nevertheless, Mmp12 represents a robust SASP factor that shows consistent age-dependent increases in expression across all tissues analyzed in this study and p16Ink4a expression is consistently increased with age in most tissues. Likewise, in humans CDKN2A (p16Ink4a) is one of the top genes exhibiting elevated expression in multiple tissues with age as revealed by data analysis of the Genotype-Tissue Expression (GTEx) project. These results support the targeting of p16Ink4a expressing-cells in senolytic treatments, while emphasizing the need to establish a panel of robust biomarkers of senescence in vivo in both mice and humans.